2007
DOI: 10.1002/pssa.200622397
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence characteristics of LiCaAlF6:Eu phosphor

Abstract: A simple method for preparing LiCaAlF6:Eu2+ phosphor is reported. Photoluminescence (PL) and thermoluminescence (TL) studies were carried out. The TL sensitivity of the phosphor is nearly twice that of CaSO4:Dy TLD phosphor. Several other properties required for TL dosimetry are superior as well. It is suggested that the phosphor can be a suitable replacement for CaSO4:Dy. (© 2007 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
2
15
1
Order By: Relevance
“…Lines at 2.0367, 2.0871, 3.615 and 3.698Å characteristic of LaF 3 are not at all seen and the pattern shows excellent match with ICDD file 87-0975. Thus, in contrast to the results on complex fluorides like LiCaAlF 6 [11], Ca 0.65 La 0.35 F 2.35 is not formed during the first stage of wetchemical preparation, but annealing at high temperature is necessary. Fig.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Lines at 2.0367, 2.0871, 3.615 and 3.698Å characteristic of LaF 3 are not at all seen and the pattern shows excellent match with ICDD file 87-0975. Thus, in contrast to the results on complex fluorides like LiCaAlF 6 [11], Ca 0.65 La 0.35 F 2.35 is not formed during the first stage of wetchemical preparation, but annealing at high temperature is necessary. Fig.…”
Section: Resultscontrasting
confidence: 67%
“…In recent years, some wet chemical processes for the synthesis of OH À free fluorides have been described [9,10]. We have successfully used these methods for synthesizing various fluorides [11][12][13][14] Use of chlorides as starting material helps in preventing the hydrolysis. Hence, complex fluorides were prepared by dissolving the analytical reagent grade chlorides of the constituent metals in the stoichiometric ratios in double distilled water in a PTFE container.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium sulfide codoped with europium and Sm/Pr 3+ are well-known infrared converting phosphors [16,17]. Intense thermoluminescence was found in Eu 2+ activated phosphors like LiCaAlF 6 :Eu [18] and K 2 Ca 2 (SO 4 ) 3 :Eu [19] which can be useful in dosimetry of ionizing radiations and related applications.…”
Section: Introductionmentioning
confidence: 98%
“…Gektin et al [19] presented detailed results on scintillation properties and thermoluminescence of LiCaAlF 6 :Ce 3+ . Recently, Aghalte et al have reported efficient TL in LiCaAlF 6 :Eu 2+ [20]. Similarly, presence of other likely phases such as CaAlF 5 , etc., was also ruled out.…”
Section: Licaalfmentioning
confidence: 94%